Outside‐in regulation of the readily releasable pool of synaptic vesicles by α2δ‐1. Issue 1 (30th November 2019) - Martínez San Segundo, Pablo; Terni, Beatrice; Burgueño, Javier; Monroy, Xavier; Dordal, Albert; Merlos, Manuel; Llobet, Artur
Abstract: The readily releasable pool (RRP) of synaptic vesicles is a key determinant of phasic neurotransmission. Although the size of the RRP is tightly regulated by intracellular factors, there is little evidence for its modification by extracellular signals. By studying the homogeneous population of synapses present in autaptic microcultures, we show that pregabalin, a prototypical gabapentinoid, decreases the effective RRP size. Simultaneous imaging of presynaptic calcium influx and recording of postsynaptic responses shows that the effect is not related to a reduction of calcium entry. The main cause is the impairment of the functional coupling among N‐type calcium channels and the RRP, resembling an increase of intracellular mobile calcium buffers. The ectodomain of neurexin‐1α shows a similar action to pregabalin, acting as an endogenous ligand of α2δ‐1 that reduces the RRP size without affecting presynaptic calcium influx. The regulatory actions described for pregabalin and the ectodomain of neurexin‐1α are mutually exclusive. The overexpression of α2δ‐1 enhances the effect of pregabalin and the ectodomain of neurexin‐1α on neurotransmission by decreasing their effective concentration. In contrast, knockdown of α2δ‐1 causes a profound inhibition of synaptic transmission. These observations prompt to consider α2δ‐1 as an outside‐in signaling platform that binds exogenous and endogenous cues for regulating the coupling of voltage‐gated calcium channels to synaptic vesicles.